Spatial variability of denitrification enzyme activity and actual denitrification emissions on Missouri claypan soils. Issue 6 (8th September 2022) - Johnson, Frank E.; Lerch, Robert N.; Motavalli, Peter P.; Veum, Kristen S.; Scharf, Peter C.
Abstract: Denitrification in agricultural soils is responsible for the majority of anthropogenic N2 O production. The objective of this research was to assess denitrification potential and the spatial dependence of soil N2 O flux from claypan soils in the Central Claypan Region of Missouri. Surface soil samples (0–10 cm) were collected on a 90‐m grid from two claypan fields, one conventionally managed in a corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotation with tillage and without cover crops (Field 1), and the other managed as a corn–soybean–wheat ( Triticum aestivum L.) rotation with no‐till and cover crops (Field 3). The denitrification enzyme activity (DEA) protocol was used to measure denitrification potential and actual soil denitrification rates of N2 O and N2 were measured with the N‐free atmospheric recirculation method (N‐FARM). In both fields, DEA fluxes were highest in the toeslope, with a rate of 1.4 kg N ha –1 d –1 in Field 1, and 1.8 kg N ha –1 d –1 in Field 3. Actual denitrification was dominated by N2 (>85%) rather than N2 O emissions, and it was considerably lower than DEA. Actual N2, N2 O, and total denitrification (N2 + N2 O) fluxes were not different between fields; however, only total denitrification flux showed an effect of landscape position similar to that of DEA in both fields. Although the high smectitic clay content of upland soils provides environmental conditions suitable for denitrification, these results indicate that the accumulation of soil C in the toeslope position controlled DEA and actual denitrification rates. Core Ideas: Changes in soil properties across landscape position influenced denitrification variability. N2 accounted for >85% of total denitrification emissions. Denitrification enzyme activity did not adequately predict actual denitrification.